2001
DOI: 10.1002/ajpa.1103
|View full text |Cite
|
Sign up to set email alerts
|

Determining isotopic life history trajectories using bone density fractionation and stable isotope measurements: A new approach

Abstract: A number of recent studies have attempted to trace diet at different stages of an individual's life by comparing isotope ratios of bone from different gross anatomical sites within the skeleton. In this study we develop this approach further by separating bone of differing mineral densities within one skeletal element, where each density fraction represents a different period of time. Isotope ratios are measured for these fractions. Each density fraction represents a period of bone formation and maturation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 68 publications
2
62
0
Order By: Relevance
“…Many osteons and packets of differing ages or maturation states exist together in one bone element, and the mineral density of younger ones are lower than that of older ones (Fratzl et al, 2004). Bell et al (2001) separated fractions of differing mineral densities within one skeletal element, in which each density fraction represented a different period of time, and applied stable carbon isotope analysis to collagens extracted from these fractions. Although they did not reconstruct BWPs, their analyses of one modern bovine bone and five archaeological human skeletons indicated that this method is potentially valuable for investigating dietary changes over years.…”
Section: The Osteological Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Many osteons and packets of differing ages or maturation states exist together in one bone element, and the mineral density of younger ones are lower than that of older ones (Fratzl et al, 2004). Bell et al (2001) separated fractions of differing mineral densities within one skeletal element, in which each density fraction represented a different period of time, and applied stable carbon isotope analysis to collagens extracted from these fractions. Although they did not reconstruct BWPs, their analyses of one modern bovine bone and five archaeological human skeletons indicated that this method is potentially valuable for investigating dietary changes over years.…”
Section: The Osteological Paradoxmentioning
confidence: 99%
“…Although they did not reconstruct BWPs, their analyses of one modern bovine bone and five archaeological human skeletons indicated that this method is potentially valuable for investigating dietary changes over years. The methods proposed by Waters-Rist et al (2010) and Bell et al (2001) are partial if not thorough solutions for the osteological paradox in BWP reconstruction. In BWP reconstruction, these methods are only applicable to subadult bones because the macro-and microstructures of bone reflecting diets in infancy would not remain until adulthood as a result of the continuous remodeling of bone (Hedges et al, 2007;.…”
Section: The Osteological Paradoxmentioning
confidence: 99%
“…However, this type of signature is geographically crude as an indicator of movement, but one that might be usefully exploited amongst other isotopic signatures. New methodologies concerning temporal sampling of the incremental tissues of bone and teeth have been developed (11)(12)(13) including the recovery of bone collagen formed close to death (14).…”
Section: Introductionmentioning
confidence: 99%
“…Herman and Richelle 8 first introduced the density fractionation method, which is a well-established method in mineral analysis, to modern bone and dental tissues with respect to age, nutrition and disease using mixtures of toluene and bromoform. Bell et al 9 drew the idea of fractionating bone density from a contemporary biomedical research tool to archaeological bone. 10 They applied this method to bones, which are known to undergo significant diet change during their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…In order to apply the bone density fractionation method to palaeodietary research, two main factors should be assured: the factors influencing density differences and those related to obtaining reliable particle size. First, differences in bone density may occur for two main reasons, i.e., bone maturation caused by metabolism in vivo 9,12 and exogenous mineralization caused by microbacterial attack after burial. 13,14 The increase in bone density in vivo is closely related to bone formation and maturation, during the continuous remodelling of bone that occurs throughout life.…”
mentioning
confidence: 99%